The Role of School Counselors in Placement Programs in Senior High Schools: A Comparative Study - Azwar, Beni (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2022)
This research aims to examine the role of School Counselors in placement and distribution services by comparing two patterns, namely majors in the 2013 Curriculum at SMAN 5 Bengkulu and subject selection in the Merdeka Curriculum at SMAN 3 Bengkulu Selatan. The research methodology used is a comparative approach with a qualitative descriptive method, using in-depth interviews with School Counselors as participants regarding the patterns used by the two schools. The first study's results show that School Counselors at SMAN 5 Bengkulu with the 2013 curriculum are more active and understand the typical yearly majoring pattern for Class X students. The data used are recommendations from the originating junior high school, parental support, and psychological test results that are not available. Alums and professionals who provide information and motivation are brought in to strengthen the process. The weakness is that choosing majors in SNPTN must consider the value of science majors such as Mathematics, Physics, Biology, and Chemistry. On the other hand, School Counselors at SMAN 3 Bengkulu Selatan, with the independent Merdeka curriculum, must be more innovative and creative in subject selection carried out in Grade XI. The data used is a majoring questionnaire with a choice of 5 subjects (3 in science and 2 in social studies, or 2 in science and 3 in social studies), and each choice is adjusted to the majors to be taken, with one subject choice for each major in tertiary institutions. Psychological test results that still need to be available in the school and a questionnaire signed by parents are also required. The difficulty lies in moving classes simultaneously, as well as differences in the wishes of parents and children.